2018
DOI: 10.1002/pssa.201800460
|View full text |Cite
|
Sign up to set email alerts
|

Impedance and Photosensitivity Spectra of Nanocomposite Structures Based on Layered Semiconductor InSe and Ionic Salt RbNO3

Abstract: Photoelectric properties of vertical ionotronic nanostructures based on layered semiconductor InSe and ionic salt RbNO3 are investigated. It is shown that the nanostructures consisting of 2D InSe layers, ultrathin layers of In2O3 oxide, and ionic salt ring‐shaped nanostructures, which are located in the (0001) planes of InSe crystal and periodically along its crystallographic C axis, have a high photosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Photoconductivity spectra of InSe<RbNO 3 > investigated in earlier studies [18] revealed significant photosensitivity at hν < E g , which is higher than that in InSe single crystals. This was ascribed to the formation of a nanotextured interface between the ionic salt and layered crystal, as well as to the peculiarities of photoconductivity in anisotropic materials.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Photoconductivity spectra of InSe<RbNO 3 > investigated in earlier studies [18] revealed significant photosensitivity at hν < E g , which is higher than that in InSe single crystals. This was ascribed to the formation of a nanotextured interface between the ionic salt and layered crystal, as well as to the peculiarities of photoconductivity in anisotropic materials.…”
Section: Introductionmentioning
confidence: 77%
“…Atomic force microscopy (AFM) imaging of the vdW surfaces of InSe and GaSe crystals after insertion of ionotronic salts revealed the presence of nanodimensional 3D inclusions of ferroelectric phases. For the GaSe<RbNO 3 > structure, a pyramidal form was identified [17,20], whereas in the case of InSe<RbNO 3 >, small islands of ionic salt were observed which created nanosized rings with an outer diameter less than 50 nm [18]. Their height did not exceed the width of vdW gap (~3.5 Å) and the surface density in the plane (0001) ranged between 10 9 and 10 10 cm −2 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations